ISFRAM 2014 Proceedings of the International Symposium on Flood Research and Management - Abu Bakar, Sahol Hamid; Tahir, Wardah; Wahid, Marfiah Ab; Mohd Nasir, Siti Rashidah; Hassan, Rohana (Springer Nature Singapore : Imprint: Springer, 2015)
This book highlights research in flood related areas and sustainable management conducted by researchers around the world, compiling their innovative work in order to share best practices for managing floods and recommended flood solutions. The individual papers cover the fundamentals and latest advances in the areas of flood research and management, providing in-depth coverage complemented by illustrations, diagrams and tables. The book offers a valuable source of information on methods and state-of-the art technology for effective flood management.